1998
DOI: 10.1046/j.1523-5378.1998.08703.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Protein Profiles of Helicobacter pylori Isolated from Individual Patients

Abstract: These findings suggest that more than one antigenically different strain of H. pylori may exist in same infected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Yakoob et al (2000) showed that two different H. pylori strains coexist in an infected individual and may not be uniformly distributed among biopsy sites [33]. Heterogeneity of protein profile of H. pylori isolated from individual patients was shown by Kitamoto et al (1998) [34]. Heterogenic nature of H. pylori strains among infected couples has also been reported from Taiwan [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yakoob et al (2000) showed that two different H. pylori strains coexist in an infected individual and may not be uniformly distributed among biopsy sites [33]. Heterogeneity of protein profile of H. pylori isolated from individual patients was shown by Kitamoto et al (1998) [34]. Heterogenic nature of H. pylori strains among infected couples has also been reported from Taiwan [35].…”
Section: Discussionmentioning
confidence: 99%
“…PCR- amplified vacA segments were digested with Hae III (Bangalore Genei) for 3 hrs at 37°C in the appropriate buffer recommended by the supplier and the digested DNA were analyzed on ethidium bromide stained 2% agarose gel [34], [43], [44]. PCR amplification of the vacA gene fragment was done using primers vas1F and vasGR [45].…”
Section: Methodsmentioning
confidence: 99%
“…Multiple infections by different strains of Hel. pylori (Beji et al, 1989 ;Owen et al, 1993 ;Fujimoto et al, 1994 ;Akopyants et al, 1995 ;Taylor et al, 1995 ;, as well as localized mixed occurrences (Kitamoto et al, 1998 ;J. C. Atherton, unpublished) have been reported, but there is no evidence that these strains compete via exponential growth.…”
Section: Discussionmentioning
confidence: 99%